Impact of Charged Particle Exposure on Homologous DNA Double-Strand Break Repair in Human Blood-Derived Cells - Rall, Melanie; Kraft, Daniela; Volcic, Meta; Cucu, Aljona; Nasonova, Elena; Taucher-Scholz, Gisela; Bönig, Halvard; Wiesmüller, Lisa; Fournier, Claudia (Frontiers in Oncology, 2015)
Ionizing radiation generates DNA double-strand breaks (DSB) which, unless faithfully repaired, can generate chromosomal rearrangements in hematopoietic stem and/or progenitor cells (HSPC), potentially priming the cells towards a leukemic phenotype. Using an enhanced green fluorescent protein (EGFP)-based reporter system, we recently identified differences in the removal of enzyme-mediated DSB in human HSPC versus mature peripheral blood lymphocytes (PBL), particularly regarding homologous DSB repair (HR). Assessment of chromosomal breaks via premature chromosome condensation or γH2AX foci indicated similar efficiency and kinetics of radiation-induced DSB formation and rejoining in PBL and HSPC. Prolonged persistence of chromosomal breaks was observed for higher LET charged particles which are known to induce more complex DNA damage compared to X rays. Consistent with HR deficiency in HSPC observed in our previous study, we noticed here pronounced focal accumulation of 53BP1 after X-ray and carbon ion exposure (intermediate LET) in HSPC versus PBL. For higher LET, 53BP1 foci kinetics were similarly delayed in PBL and HSPC suggesting similar failure to repair complex DNA damage. Data obtained with plasmid reporter systems revealed a dose- and LET-dependent HR increase after X-ray, carbon ion and higher LET exposure, particularly in HR-proficient immortalized and primary lymphocytes, confirming preferential use of conservative HR in PBL for intermediate LET damage repair. HR measured adjacent to the leukemia-associated MLL breakpoint cluster sequence in reporter lines revealed dose-dependency of potentially leukemogenic rearrangements underscoring the risk of leukemia-induction by radiation treatment.